COMPARISON OF NASOLABIAL ANGLE IN YOUNG ADULTS AND MIDDLE AGED DENTATE AND ELDERLY EDENTULOUS SUBJECTS: Nasolabial Angle - A Comparative Study - Azad, Lt Col Azad Ali; Akhtar, Qayyum; Ibrahim, Shazia Zareen Aqeel; Aziz, Faisal; Hasan, Syed Hammad (Pakistan Armed Forces Medical Journal, 2010)
Objective: To compare the mean value of nasolabial angle in dentate and edentulous subjects in young adults, middle aged dentate (having normal occlusion) and elderly edentulous subjects. Study Design: Cross-sectional comparative study Place and Duration of Study: The study was conducted in the Department of Prosthodontics, Armed Forces Institute of Dentistry, and Army Medical College, Rawalpindi from September 2007 to November 2008. Patients and Methods: A total of 250 subjects were divided in three age groups. Group 1: 100 Subjects 20–30 years , Group 2: 100 subjects 35-45 years and Group 3: 50 edentulous subjects >50 years. The subjects with Intact maxillary and mandibular arches and Angle’s Class-I molars, canine and incisor relationship were included. Standard lateral cephalometric radiographs of the heads were traced and nasolabial angle was measured. Results: The mean values of nasolabial angle in dentate and edentulous were 96.79°±2.6 and 111.40o±2.51respectively. The mean values of nasolabial angle in young adults (20-30 years), middle aged (35-45 years) and old edentulous (>50 years) subjects were 97.39o±2.94, 96.19o±2.58 and 111.40o±2.51respectively. The difference in mean values of nasolabial angle among three groups, was statistically significant (p<0.001). Conclusions: Nasolabial angle in middle aged subjects is greater than younger subjects and even greater in elderly edentulous subjects. Sexual dimorphism exists as males have greater nasolabial angle in younger age. While fabricating dental prosthesis nasolabial angle may be restored near to the dentate subjects.